Immunoaffinity purification of dietary heterocyclic amine carcinogens. - Vanderlaan, M (1993)
Cooking meats produces a family of heterocylic aromatic amines that are carcinogens in rodents and genotoxic in many short-term assays. Concern that these compounds may be human carcinogens has prompted us to develop immunochemical methods for quantifying these compounds in the human diet and for identifying the parent compounds and metabolites in urine and feces. Previously reported monoclonal antibodies to 2-amino-3,8-dimethylimidazo[4,5-f]quinoxaline (MeIQx) and 6-phenyl-2-amino-1-methylimidazo[4,5-f]pyridine (PhIP) were used to purify by immunoaffinity these known mutagens and cross-reacting structural analogs from well-done cooked beef and urine samples. Materials recovered from the immunoaffinity columns were subsequently separated by HPLC to purify the known mutagens from cross-reacting chemicals that co-purify by immunoaffinity. Immunoaffinity chromatography was found to be a rapid means of quantifying individual known mutagens, with a minimum of precolumn sample clean-up required. In addition, this procedure has yielded several new mutagens present in cooked meats that are apparently structural analogs of PhIP. Immunoaffinity techniques were also used to purify metabolites from the urine of rats and humans exposed to MeIQx or PhIP. For MeIQx-exposed rats, the combination antibodies immunoconcentrated 75% of the total urinary radioactivity. Analysis of PhIP metabolites recovered from antibody columns is facilitated by the intrinsic fluorescence of PhIP and its metabolites, providing sufficient sensitivity to monitor individuals for the levels of PhIP excreted following consumption of typical western diets.